Metal-Polymer Sensors for Voltammetric Analysis; Key Engineering Materials; Vol. 670 : Multifunctional Chemical Materials and Technologies - Shelkovnikov V. Vladimir V.; Anishchenko M. V. Mikhail V.; Anishchenko Yu. V. Yuliya Vladimirovna; Minaev K. M. Konstantin Madestovich (2015, 2015)
Title screen